INTENSIFIERS IN ITALIAN IN TRANSIT: TRACING BIOGRAPHICAL EXPERIENCES THROUGH LANGUAGE PRACTICES - Marta Lupica Spagnolo (Italiano LinguaDue)
This paper explores strategies of morphological/lexical intensification in Italian-based multilingual practices I label ‘Italian in Transit’ (IiT). IiT is informally acquired by plurilingual migrants and refugees in Italy and occasionally reactivated after onward migration. This study draws on 23 interviews with IiT speakers from sub-Saharan West Africa working as street vendors in a Berlin park. After outlining the intensifiers used in my corpus, I focus on two largely interchangeable forms in Italian: molto and tanto ‘very/much/many’. In reverse to their distribution across all registers in reference corpora for spoken Italian, tanto significantly outnumbers molto in my data (though their part-of-speech distribution matches that of the target language). This predominance reflects the frequency patterns of the two intensifiers in informal spoken registers only. Thus, it may be a linguistic trace of the input participants were mainly exposed to in Italy and their biographical experiences. In contrast, other sociolinguistic factors, like the length of stay in Italy or Germany, show no decisive impact. The paper also examines the occasional use of troppo ‘too much/many’ to convey high intensity rather than excess. IiT partly shares this feature with Italian youth varieties, colloquial French, and some Italian-based contact varieties developed outside Italy. Despite considerable interspeaker variation, troppo usually occurs in re-elaborative sequences and is often preceded by strategic pauses. Its overextension – also observed in non-French-speaking participants – is therefore linked to its discourse-pragmatic and prosodic salience.